KEY ISSUES OF ASSESSING FINANCIAL STABILITY IN THE REPUBLIC OF ARMENIA - Tepoyan, Vahagn (Bulletin of Yerevan University G: Economics, 2020)
Nowadays, the growth of financial instability due to diverse factors in global financial markets is forcing economists to find solutions for quantitatively measuring, assessing, and predicting financial stability. The article describes the current approaches for determining, evaluating and modeling of financial stability and a methodological approach has been suggested for assessing the financial stability of the Republic of Armenia, based on an index that has been calculated taking into account fifteen macroeconomic indicators. Using the suggested methodological approach, the state of the financial stability of the Republic of Armenia, as well as the internal and external threats have been assessed.